Software-Defined Wireless Mesh Networking: Current Status and Challenges. (13th July 2017) - Rademacher, Michael; Jonas, Karl; Siebertz, Florian; Rzyska, Adam; Schlebusch, Moritz; Kessel, Markus
Abstract: The combination of Software-Defined Networking (SDN) and Wireless Mesh Network (WMN) is challenging due to the different natures of both concepts. SDN describes networks with homogeneous, static and centralized controlled topologies. In contrast, a WMN is characterized by a dynamic and distributed network control, and adds new challenges with respect to time-critical operation. However, SDN and WMN are both associated with decreasing the operational costs for communication networks which is especially beneficial for internet provisioning in rural areas. This work surveys the current status for Software-Defined Wireless Mesh Networking. Besides a general overview in the domain of wireless SDN, this work focuses especially on different identified aspects: representing and controlling wireless interfaces, control-plane connection and topology discovery, modulation and coding, routing and load-balancing and client handling. A complete overview of surveyed solutions, open issues and new research directions is provided with regard to each aspect.